Coordinated targeting of cold and nicotinic receptors synergistically improves obesity and type 2 diabetes - Christoffer Clemmensen (Nature Portfolio, 2018)
Tobacco smoking and cold exposure are environmental modulators of human energy metabolism suppressing appetite and increasing energy expenditure, respectively. Here, the authors develop a novel pharmacological strategy in which they simultaneously mimic the metabolic benefits of both phenomena through small-molecule combination therapy, and show that this treatment improves metabolic health of obese mice.